UK Fisheries Audit: Report for Oceana - Guille, Heidi; Gilmour, Caitlin; Willsteed, Edward; MacAlister Elliott & Partners; Oceana (Zenodo, 2021)
The UK’s decision to leave the EU and to regain control of its waters has enormous implications for the management of North East Atlantic Fisheries. The results derived from the implementation of new UK domestic regulations and international fisheries agreements will have a direct impact on the status of fish stocks and the socio-economic performance of fishing fleets. There is an opportunity and a responsibility for the UK, as an independent coastal state for the first time in over 40 years, to lead the way in achieving sustainable fisheries. The key objective of this report is to provide an evidence-based snapshot of the status of UK fish stocks and the UK fishing sector’s recent exploitation history of those stocks, by the time the UK abandons the EU fisheries policies. In doing so, the report provides a baseline for future evaluations of the UK’s progress and/or setbacks in sustainable fisheries management. The turnover of UK fisheries in 2019 was about £1 billion with the majority derived from over 24m vessels operating from Scotland. The majority of UK fisheries landings from the North East Atlantic in 2019 (618,000 t) came from UK waters (81% by live weight or around 500,000t and 87% by value). Around 27% of EU catches in the North East Atlantic were also typically taken from UK waters between 2012 and 2016, amounting to approximately 700,000 tonnes[1]. Stocks critical to UK fisheries include quota and non-quota species, with the latter not subject to EU Total Allowable Catches (TACs) – the primary management mechanism for North East Atlantic fisheries. Pelagic quota species such as mackerel and herring caught by over 10m vessels dominate UK landings by volume (54%). Non-quota shellfish such as scallops and crab are also key contributors (21%), with the remaining 25% comprised of demersal species. Smaller inshore vessels (10m and under) which dominate the UK fleet by number (74%), rely on non-quota species (shellfish comprise >80% of landings by volume and value). Of the 104 UK stocks audited, 82 of which are quota stocks shared mainly with the EU, 35.6% were healthy in terms of stock size (43.9% of shared stocks) relative to the MSY reference point B trigger , whereas 20.2% were in a critical condition (15.9% of shared stocks). Data limitations mean the status of the remaining 44.2% (40.2% of shared stocks) cannot be determined, leaving them at greater risk of unsuitable management decisions. Analysis of the exploitation status revealed that 37.5% of the audited stocks were sustainably exploited prior to the UK leaving the EU (42.7% of the 82 shared stocks). However, 28.8% were being overfished (25.6% of the shared stocks) (F>F MSY ), whilst another 33.6% were data limited and so cannot be adequately assessed (31.7% of shared stocks). In order that the implications of any management actions or policy decisions by the UK government following Brexit can be considered in greater depth, more detailed benchmarks for a selection of stocks are provided. Those stocks were selected according to their economic status (the ‘top 10’) or their performance: the 5 most sustainably and 5 most unsustainably fished in terms of stock size and fishing mortality rate. Separately, a more detailed examination of the recent exploitation and management history of all the cod stocks fished by the UK is provided given ongoing concerns over the status of this iconic fish species. Only 3 of the ‘top 10’ were healthy and sustainably exploited (North East Atlantic mackerel, North Sea haddock and West of Scotland Nephrops). Two of the stocks are overexploited and their biomass is below safe biological reference points as a result (North Sea cod, Southern North Sea edible crab). For the remaining stocks there is a mixed picture, including data limitations for North Sea anglerfish (monkfish) and scallops in the English Channel. The 5 best performing stocks are typically caught in relatively small quantities and are of relatively low value to the UK fishing industry, except for Western English Channel common sole which attracted the highest price per tonne of all the focus stocks. Zero catches have been advised for 3 of the 5 worst performing stocks – Irish Sea whiting and cod in the Celtic Sea and West of Scotland. The challenges of rebuilding depleted stocks are highlighted by a focus on the cod stocks. North Sea cod is once again subject to emergency management measures. With climate change also likely to be affecting cod’s resilience to fishing mortality, effective recovery plans are needed more urgently than ever. However, because the majority of the cod stocks are primarily caught as bycatch in valuable mixed fisheries, such measures will require a shift in fisheries management priorities. Lagging full policy implementation and persistent political decisions to set TACs above scientifically advised catch levels are still pending issues for fisheries management, and key contributing factors to the ongoing overfishing of North East Atlantic fish stocks, including Atlantic cod. For the ‘top 10’ and 5 worst performing stocks, the majority of TACs for the period 2016-2020 were set above levels advised by ICES. Conversely, the TACs for the top performing stocks were mainly set at, or commonly below, scientifically advised levels . The report investigates a number of other specific issues associated with UK fisheries and their management which have negative implications for the environment and sustainable fishing. Potential opportunities for improvements following the UK’s departure from the EU, as well as further risks, are highlighted. For example, the UK has the opportunity to demonstrate better practice by accommodating the ecological importance of species when implementing or influencing future management strategies, as highlighted by the implications of overfishing of sandeels for the North Sea fish, cetacean and seabird populations. In response to the findings of the UK fisheries audit, Oceana sets out policy recommendations for the UK Government. Overarching to these is ensuring sustainable fisheries is the primary goal of the UK’s fisheries policies and plans, in order to fulfil the objectives of the UK Fisheries Act and achieve the UK government’s aspiration to set ‘a gold standard for sustainable fishing around the world’, as well as meeting UK international biodiversity and sustainability commitments. [1] Data for the non-UK fleet in UK waters are not available for the period since 2016.